Top 100 Most-Cited Papers in Substance Abuse: A Bibliometric Analysis and Evidence Mapping - MartÃn-del-RÃo, Beatriz; GarcÃa-Selva, Adrián; Cortés-Tomás, MarÃa-Teresa; Giménez-Costa, José-Antonio; GÃ³mez-ÃÃ±iguez, Consolación (Revista Cubana de Información en Ciencias de la Salud, 2024)
The citations of an article reflect its impact, recognition and influence in the scientific and professional community, as well as providing a way of understanding the socio-organisational structure, in this case of the area of substance abuse research. The objective is to analyse the 100 most cited articles in the Web of Science, which have been published in journals in the Substance Abuse category of the Journal Citation Reports. The methods applied are retrospective bibliometric analysis and scientific mapping. Forty journals were identified in the category "Substance Abuse". A WOS search was conducted and the 100 most cited articles were selected. Title, authors, institutions, countries, year and citations were extracted from WoS. JCR impact factor, citation density, immediacy index, quartile and country were calculated. Citation density and Bradford's law were calculated, and studies were classified according to their design and topic. All studies analysed are citation classics published over 40 years, and the most recent ones were the most cited. The most frequent design was review, while longitudinal and randomised control studies were rare. In terms of subject matter, substance assessment and diagnosis dominated, with little representation of behavioural addictions. Authors from all five continents participated, and the majority were from the United States. Most of the studies were published in four journals with a higher average impact factor than others in related areas. There is a clear tendency to cite reviews, evaluations and diagnostic studies related to substance abuse.